Kreativitas Guru Pai Memilih Model Pembelajaran Dalam Menciptakan Situasi Pembelajaran Yang Efektif Kelas VII Di SMPN 2 Kinali - Nadia Wulandari; Muhiddinur Kamal (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research was motivated by problems identified from various factors at SMPN 2 Kinali, where many students were noisy, sleepy and had problems with their classmates. This happens because students feel bored with the subject. As a result, it weakens learning. The aim of this research is to identify how creative PAI teachers are in selecting learning forms to produce an efficient learning atmosphere for category VII students at SMPN 2 Kinali. This research is qualitative descriptive in nature. Research runs at SMPN 2 Kinali. In relation to the main sources of information, they are PAI class VII teachers at SMPN 2 Kinali, and the inferior sources of information are the class VII students of SMPN 2 Kinali and the school principal. The information collection methods used in this research are monitoring, question and answer and documentation. The results of this research prove that PAI teachers' creativity in creating an efficient learning atmosphere lies in the use of learning forms and the application of learning outside of categories to produce a supportive learning atmosphere. The teacher's creativity determines the form of learning in producing an efficient learning atmosphere, through the use of a versatile learning form which is carried out by combining several existing forms with several important views, namely: taking into account the constitution of the students, the module to be taught and the management of the form.